DISCURSIVE AND SOCIAL PRACTICES IN INSTAGRAM CAPTIONS: EVIDENCE FROM INDONESIA - Hidayana Putri; Didin Nuruddin Hidayat (Prasasti: Journal of Linguistics, 2022)
This study describes discursive and social practices in Instagram captions used by celebrity endorsers in promoting cosmetic products. This study employed a qualitative descriptive design in order to describe a critical discourse analysis. As the participants in this study, three celebrity endorsers are randomly selected based on their verified Instagram account, and they used Instagram actively for business and product promotion purposes. The data were obtained from Instagram captions of three celebrity endorsers. Additionally, this study's analysis technique is a descriptive-analytic method through the process of collecting and compiling data analysis. The data is then analyzed using a critical discourse analysis method based on Norman Fairclough’s, such as discursive practice analysis and social practice analysis. The results reveal that discursive practices applied by celebrity endorsers are utilized to motivate consumers to buy and use the products. The strategies used by celebrity endorsers are real testimonials, clinical evidence, and inspiring words. Besides, the social practice of products promoted by celebrity endorsers can have the power over society because the language used in promoting cosmetic products can trigger people’s desire to become consumers of those products. Therefore, the existence of celebrity endorsers who are healthy, beautiful, attractive, and charming can feel an emotion in the ability to control people in the beauty perspective among them.